Discursive Constructions of Patriarchy in Mulan (2020): A Study of Language, Culture, and Power - Wijaya, Ayudhia Ratna; Marsuki, Ria Riski; Pamuji, Dian Yuni (Universitas Negeri Semarang, 2025)
This study investigates the representation of Chinese patriarchal culture through linguistic expressions in Disney’s 2020 live-action film Mulan. Employing a descriptive-qualitative method and grounded in a sociolinguistic framework, particularly the intersection of language and gender, this research analyzes how patriarchal values are encoded in character dialogue. A relational analysis approach, informed by gender and family relation theories, reveals distinct speech patterns between male and female characters. Male characters predominantly use declarative and evaluative speech acts characterized by positive metaphorical expressions, signifying authority and affirmation within the societal hierarchy. Conversely, female characters’ utterances are largely expressive and commissive in nature, often marked by negative metaphors, reflecting marginalization and constrained agency. The findings suggest that patriarchal cultural norms continue to shape social expectations and restrict women’s participation in the public sphere. Within the narrative, gender roles are assigned based on biological sex rather than individual competence or evolving social identities, underscoring the persistence of gender-based power asymmetries in Chinese patriarchal discourse.